INTEGRASI ALGORITMA FISHER-YATES SEBAGAI PENGEMBANGAN E-LEARNING DI UNIT KEGIATAN BELAJAR MANDIRI - Karisma Nanda Arditya; Moh Bhanu Setyawan; Adi Fajaryanto Cobantoro (Universitas Muhammadiyah Ponorogo, 2021)
E-learning is currently very important and a must for educational institutions. Many e-learning application platforms are based on Learning Management System (LMS) that can be used by schools, whether they are open source, paid for or build their own applications. There are many considerations that must be faced when deciding to use an e-learning-based application (LMS) including infrastructure readiness, costs and application compatibility with the e-learning concept desired by educational institutions. The availability of features in the e-learning system is one that must be adjusted to the e- learning concept that will be selected. Each institution may be able to determine its own characteristics that can be specific and not yet fully accommodated in the e-learning application that currently exists. One of them is the feature to randomize exam questions to ensure that each student gets different questions with the same composition. This research will try to answer this problem by integrating the fisher-yates shuffel algorithm. The success of this algorithm integration will be assessed by conducting an exam simulation involving two classes and seeing how the system will randomly divide the exam questions to each student. The first assessment is the suitability of the composition of the questions and the similarity of the questions between students, the less students receive the same questions appearing on the exam questions, the better the system performance.